Redistribution and recognition: land reforms in Kerala and the limits of culturalism - Nissim Mannathukkaren (Journal of Peasant Studies, 2011)
The most important achievements of the Communist governments in Kerala, India were the implementation of the land reforms and the legislation of the Agricultural Workers’ Act. Using ethnographic and archival research based on these events and the processes through which they became a reality, this paper will question some of the fundamental assumptions of the influential Subaltern Studies project and postcolonial theory like the positing of governmentality and passive revolution as the general characteristics of ‘Third World’ societies’ experience with modernity. It will argue that, more importantly, their culturalist framework, with its gross ignorance of class and material concerns, is hardly adequate to understand the fusing of the aspirations of recognition and redistribution or the material and cultural that characterizes the struggles by the peasantry and agrarian labor, and their synthesis by the Communist Party. Despite their professed aim of inaugurating a democratic project with the peasant as citizen, Subaltern Studies and postcolonial theory, unlike the Communist movement, do not envisage any material transformation of the agrarian classes that will actualize this objective